2017
DOI: 10.1080/03630242.2017.1333074
|View full text |Cite
|
Sign up to set email alerts
|

Health-related behaviors moderate the association between age and self-reported health literacy among Taiwanese women

Abstract: The role of health-related behaviors in the association between age and health literacy has not been well-elucidated. The present cross-sectional study evaluated the interactions between age and health-related behaviors in 942 women in Taiwan between February and October 2013. Women aged 18-78 years were randomly sampled and recruited from the national administrative system. Self-reported health literacy was measured by the European Health Literacy Survey Questionnaire (HLS-EU-Q47) in Mandarin, asking about so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…The positive association suggests that public health interventions implemented in the country are probably effective. One notes that this factor was also found positively significant in other research [7,12,13,26,31].…”
Section: Biomed Research Internationalsupporting
confidence: 54%
See 2 more Smart Citations
“…The positive association suggests that public health interventions implemented in the country are probably effective. One notes that this factor was also found positively significant in other research [7,12,13,26,31].…”
Section: Biomed Research Internationalsupporting
confidence: 54%
“…A positive association between participating in these activities and HL was therefore expected. Community involvement associated with higher health literacy was also found in Kazakhstan [31] and Taiwan [13].…”
Section: Biomed Research Internationalmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, it is critical for the government and the ministry of health to provide accessible platforms with official and reliable information regarding the COVID-19 pandemic. In addition, it is suggested that people should enhance their life-long learning behaviors (e.g., watching health-related television programs, reading official websites) to improve individual health literacy [63]. The above may further contribute to preventing and controlling infectious diseases [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the level of health literacy was usually lower among men than women (for a review, see Davey et al 2015), despite their tendency to over-report the abilities when answering health literacy questions (Lee et al 2013a). Older women were more likely to watch health-related television programs and have social engagement, which may result in higher health literacy and better health (Duong et al 2018). However, how one's sex would moderate the effects of health literacy on health behavior and health status has been relatively unstudied.…”
mentioning
confidence: 99%